Approximate solution for Fokker-Planck equation - Araujo, M. T. [UNESP]; Drigo Filho, E. [UNESP] (Institute for Condensed Matter Physics, 2015)
In this paper, an approximate solution to a specific class of the Fokker-Planck equation is proposed. The solution is based on the relationship between the Schrödinger type equation with a partially confining and symmetrical potential. To estimate the accuracy of the solution, a function error obtained from the original Fokker-Planck equation is suggested. Two examples, a truncated harmonic potential and non-harmonic polynomial, are analyzed using the proposed method. For the truncated harmonic potential, the system behavior as a function of temperature is also discussed.
Keywords: Approximate solution; Fokker-Planck equation; Schrödinger equation